Rummaging English Idiomatic Expressions In Bohemian Rhapsody Movie - Laurent, Ria; Sugeng Nur Agung, Antonius Setyawan; Rufinus, Albert; Nurcahyoko, Kunto; Siboro, Efrika (Efektor, 2023)
Tujuan dari penelitian ini adalah untuk mengetahui bagaimana idiom bahasa Inggris digunakan dalam film Bohemian Rhapsody dengan menggunakan pengelompokan idiom berdasarkan teori Adelnia dan Dastjerdi untuk memberikan bentuk dan makna idiom dari film tersebut. Metode yang digunakan dalam The purpose of this study is to determine how English idioms are used in the film Bohemian Rhapsody by using the categorization of idioms indicated in Adelnia and Dastjerdi's theory to provide the form and meaning of the idioms from the film. It was conducted using a descriptive qualitative method. The instrument of collecting the data was dialogue from the movie Bohemian Rhapsody. The procedure of the research involved watching the movie, recognising, grouping, assessing the meaning, and determining the frequency of the idioms used. The findings of the study showed that 27,7% colloquialisms, 8,5% proverbs, 37,2% slang, 10,64% allusions, and 15,96% phrasal verbs were used in this film. The conclusions of this research can be used as an additional reference or comparison for further research, and also to encourage another researcher to provide a significant conclusion related to the topic with another point of view.